Analysis of Madrasah Principal Leadership in Improving Teacher Performance of Madrasah Aliyah Darul Ulum Waru - Huda, Alfin (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The background of this study is that the head of the madrasah shows leadership and situational influence and directs his subordinates by increasing trust, assistance, motivation, and ties to achieve the goals and objectives of the training institution, and providing guidance. In this case, improving teacher performance is a manifestation of the role of madrasa heads in improving the quality of work of educational staff. The aims of this research are: (1) To understand the role of madrasa heads in improving teacher performance at Madrasah Aliyah Darul Ulum Waru. (2) To understand what obstacles madrasah leaders face in improving teacher performance. This research applies a qualitative approach. This method was chosen because the investigation aims to describe an ongoing signal, problem or event. The topic of this investigation is madrasa heads and teaching staff. Data was collected using observation, interviews and documentation methods. Additionally, it is presented in a good format for easy reading and interpretation. The data is then analyzed and conclusions are drawn.